Secado de trozos de cocona ( solanum sossiliflorum dunal ) por aire caliente con pretratamiento de osmodeshidratación - Silvia Correa, Cindy Marilyn (2013)
In this thesis work "COCONA CUTS DRYING (Solanum sessi/if/forum Dunal) HOT AIR WITH PRETREATMENT OSMOTIC DEHYDRA TION" was searched conservation methodology cocona pieces of which were subjected to serosa solutions of 30%, 40% and 50% as pretreatment and air flow with temperatures of 40ºC, 50ºC and 60ºC (constant speed air 1.1 m/s), where the treatment of 60ºC, with 40% sucrose, has better organoleptic characteristics and greater moisture reduction (HBS) 0.022 kg H20/kg of dry solid, with contents of 2% protein, 5.98 mg of vitamin C, 1.71 % fat, 2.24% ash and 0.81% reducing sugars. The effect of temperature and concentrations of osmotic solution curves were estimated weight loss, drying speed, water activity and color, depending on the drying time (8 hours) curves were fitted with drying equation of Fick's second law and diffusivity obtained was 7.44 x 10·8 m2/s at 60ºC treatment and 40% sucrose. The best treatment was determined by sensory evaluation with 5-point hedonic scale and untrained panelists. Sensory evaluation attributes such as color, odor, flavor, texture were represented by the response surface plots. We evaluated the packaged product stored for 3 months, obtaining 10.08% moisture and water activity 0.492 presenting microbiological stability.